Chemical Composition and Antipathogenic Activity of Artemisia annua Essential Oil from Romania. Issue 10 (October 2015) - Marinas, Ioana C.; Oprea, Eliza; Chifiriuc, Mariana Carmen; Badea, Irinel Adriana; Buleandra, Mihaela; Lazar, Veronica
Abstract The essential oil extracted by hydrodistillation from Romanian Artemisia annua aerial parts was characterized by GC/MS analysis, which allowed the identification of 94.64% of the total oil composition. The main components were camphor (17.74%), α‐pinene (9.66%), germacrene D (7.55%), 1, 8‐cineole (7.24%), trans‐β‐caryophyllene (7.02%), and artemisia ketone (6.26%). The antimicrobial activity of this essential oil was evaluated by determining the following parameters: minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), minimal fungicidal concentration (MFC), and minimal biofilm eradication concentration (MBEC). Moreover, the soluble virulence factors were quantified with different biochemical substrates incorporated in the culture media. The reference and resistant, clinical strains proved to be susceptible to the A. annua oil, with MICs ranging from 0.51 to 16.33 mg/ml. The tested essential oil also showed good antibiofilm activity, inhibiting both the initial stage of the microbial cell adhesion to the inert substratum and the preformed mature biofilm. When used at subinhibitory concentrations, the essential oil proved to inhibit the phenotypic expression of five soluble virulence factors (hemolysins, gelatinase, DNase, lipases, and lecithinases). Briefly, the present results showed that the A. annua essential oil contained antimicrobial compounds with selective activity on Gram‐positive and Gram‐negative bacterial strains as well as on yeast strains and which also interfere with the expression of cell‐associated and soluble virulence factors.